Building climate-resilient agriculture for refugees and host communities in Jordan - Bioversity International and International Center for Tropical Agriculture (CIAT) (2025)
Jordan hosts one of the highest refugee populations per capita. Yet Syrian farmers struggle to access loans, land, and licenses. How can climate-smart solutions help? The CGIAR Research Initiative on Fragility, Conflict, and Migration, at the request of the World Food Programme (WFP), explored explored financing options to support climate-resilient farming, boosting food security & social cohesion.